2015
DOI: 10.1096/fj.15-274191
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid-specific deletion of dicer-dependent microRNAs abrogates the response of the parathyroid to acute and chronic hypocalcemia and uremia

Abstract: MicroRNAs (miRNAs) down-regulate gene expression and have vital roles in biology but their functions in the parathyroid are unexplored. To study this, we generated parathyroid-specific Dicer1 knockout (PT-Dicer(-/-) ) mice where parathyroid miRNA maturation is blocked. Remarkably, the PT-Dicer(-/-) mice did not increase serum parathyroid hormone (PTH) in response to acute hypocalcemia compared with the >5-fold increase in controls. PT-Dicer(-/-) glands cultured in low-calcium medium secreted 5-fold less PTH at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 46 publications
4
37
0
Order By: Relevance
“…PTH secretion, gene expression, cell proliferation and the increased PTH secretion after acute hypocalcaemia were all dependent on Dicer1. In addition, the development of sHPT of both chronic hypocalcaemia and uraemia in these mice was dependent on parathyroid miRNAs .…”
Section: Micrornasmentioning
confidence: 95%
See 1 more Smart Citation
“…PTH secretion, gene expression, cell proliferation and the increased PTH secretion after acute hypocalcaemia were all dependent on Dicer1. In addition, the development of sHPT of both chronic hypocalcaemia and uraemia in these mice was dependent on parathyroid miRNAs .…”
Section: Micrornasmentioning
confidence: 95%
“…Expression of a subset of miRNAs might discriminate between PA and PC, but this needs to be validated in larger tumour cohorts. The role of miRNAs in normal parathyroid function was recently investigated using parathyroid‐specific DICER1‐knockout mice . DICER1 deletion blocked the processing of pre‐miRNAs and thereby prevented mature miRNA expression in general.…”
Section: Micrornasmentioning
confidence: 99%
“…The PT-Dicer À/À mice also had an impaired increase in serum PTH, PTH mRNA, and parathyroid cell proliferation after both chronic hypocalcemia and uremia. 8 Therefore, miRNAs are essential for the stimulation of the parathyroid by hypocalcemia and uremia. miRNA profiling by deep sequencing in parathyroid glands from experimental hyperparathyroidism models and patients receiving dialysis showed that human and rodent parathyroids share similar miRNA profiles.…”
Section: See Basic Research On Page 54mentioning
confidence: 99%
“…Altered expression of miRNAs may well have an important role in development of parathyroid tumors and miRNAs have been implicated in parathyroid function. Dicer-dependent maturation of parathyroid miRNAs is responsible for the dysregulated control of PTH secretion in a uremic mouse model of secondary hyperparathyroidism (Shilo et al, 2015 ). However, specific miRNAs that directly affect parathyroid CaSR expression have yet to be identified.…”
Section: The Casr Genementioning
confidence: 99%